2017
DOI: 10.1074/mcp.m116.063602
|View full text |Cite
|
Sign up to set email alerts
|

A Human Proteome Array Approach to Identifying Key Host Proteins Targeted by Toxoplasma Kinase ROP18

Abstract: Toxoplasma kinase ROP18 is a key molecule responsible for the virulence of Toxoplasma gondii; however, the mechanisms by which ROP18 exerts parasite virulence via interaction with host proteins remain limited to a small number of identified substrates. To identify a broader array of ROP18 substrates, we successfully purified bioactive mature ROP18 and used it to probe a human proteome array. Sixty eight new putative host targets were identified. Functional annotation analysis suggested that these proteins have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 94 publications
2
19
0
Order By: Relevance
“…Among the ROP18 I -interacting proteins, CNBP, DCTD, NUP160, and PRAC, which had been previously confirmed as ROP18 I -interacting proteins by a previous human proteome array ( 22 ), were also identified in our HT-BiFC assay, indicating the reliability and quality of our results. In addition to these known interactions, 488 interactions of ROP18 I with human proteins were newly defined in our study.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Among the ROP18 I -interacting proteins, CNBP, DCTD, NUP160, and PRAC, which had been previously confirmed as ROP18 I -interacting proteins by a previous human proteome array ( 22 ), were also identified in our HT-BiFC assay, indicating the reliability and quality of our results. In addition to these known interactions, 488 interactions of ROP18 I with human proteins were newly defined in our study.…”
Section: Resultssupporting
confidence: 73%
“…However, YTH generates a high occurrence of false positives and requires that the interacting proteins accumulate in the yeast nucleus ( 21 ). More recently, by using a protein array approach, Yang et al have identified 68 substrates of the Tg ROP18 kinase, and four of them have been validated as the host targets ( 22 ). Although protein array is useful for comprehensive screens of protein functions, it requires pure functional proteins that are difficult to obtain because of the difficulties in expressing the proteins in a soluble form with correct folding ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth in vivo studies confirmed that these phosphorylation events played an important role in promoting viral DNA replication in all four viruses. In another study, we observed that a secreted protein kinase ROP18, encoded by Toxoplasma gondii, could phosphorylate multiple components in the MAPK pathway [29]. A third example is the observation that KSHV-encoded LANA protein could bind to all three components of the NER damage recognition/verification complex XPA-RPA (i.e., XPA, RPA1 and RPA2) [47].…”
Section: Discussionmentioning
confidence: 97%
“…The Human Proteome Microarray v3.0 (HuProt TM array), comprised of 20,240 immobilized human proteins from >15,000 full-length genes, was used to identify human-viral PPI networks [29]. Each viral protein was fluorescently labeled and individually probed to the HuProt array.…”
Section: Construction Of Zikv-and Denv-human Ppis With Huprot Tm Arraymentioning
confidence: 99%
“…It has been reported that overexpression of Tg ROP18 significantly suppresses human embryo kidney epithelial cell 293T apoptosis induced by Actinomycin D at 48hrs post transfection [15], and Tg ROP18 targets P53 for degradation to inhibit host cell apoptosis [30]. On the contrary, Tg ROP18 is also reported to induce the apoptosis of murine neuroblastoma N2a cells through the endoplasmic reticulum stress-mediated apoptosis pathway at 24hrs post infection [14].…”
Section: Discussionmentioning
confidence: 99%